(untitled) (Bombay Hospital Journal, 2024)
Aim-We would like to present our experience in managing SIH with Chronic SDH which required multimodality treatment. Background-Spontaneous intracranial hypotension usually occurs due to CSF leak from ,causing overall decrease in CSF volume .Incidence reported is 5/100000 population per year(1).But lacks typical symptomatology.It can occur in any age group with female preponderance with ratio 1.5-2:1.CSF leak may be due to dural tear,meningeal diverticulum and CSF-venous fistulas(1) in dorsal-lumbar region.SIH causes sagging of brain causing subdural spacing and SDH. Case Description - A middle aged male patient presented with orthostatic headache with history of epidural catheter in the past.After detailed clinical evaluation patient was advised for MRI brain with whole spine screening,which showed Chronic Subdural hematoma (SDH) with thoracic epidural CSF collection.Patient was evaluated and underwent multimodality treatment with surgical burr hole evacuation of SDH,epidural blood patch for epidural CSF leak and medical management with Tranexemic acid .On 4 weeks follow up,patient did not have any symptoms and 9 months follow up showed no symptoms and no recurrence on CT scan. Conclusion- SIH with SDH usually needs multiple mode of treatment.Our step up plan from conservative to multimodality management benefitted the patient with complete resolution of symptoms and complete resolution of SDH